‘Wat bedroeft lot is oudt stijf ende arm te wesen’ Waardigheid in verzoekschriften van verarmde Brusselse ouderen, c. 1750-1800. - Verbeke, Anke (TSEG - The Low Countries Journal of Social and Economic History, 2019)
‘How sad a fate to be old, stiff and poor’. Deservingness in almshouse applicationletters by impoverished Brussels elderly ca. 1750-1800.This article offers a bottom-up perspective to the research on inclusion processes inpoor relief in general and elderly care and almshouses in specific at the end of theAncien Régime. By means of an extensive study of the application letters sent to theBrussels ‘Twaalf Apostelen’ almshouse between 1750 and 1800, the article examineshow deservingness is anticipated by the elderly applicants and how it is argued intheir discourses. In addition, the article offers insight into the mental framework ofthese elderly men surrounding coping strategies and channels through which careshould or could be obtained. By doing this, the article examines to which extent processesof formalization during previous centuries influenced the mental frameworkof the elderly during the second half of the eighteenth century.